2017
DOI: 10.7150/jca.17595
|View full text |Cite
|
Sign up to set email alerts
|

The tumor microenvironment and inflammatory breast cancer

Abstract: Inflammatory breast cancer (IBC) is a rare and very aggressive subtype of breast cancer with clinical manifestations similar to acute inflammation. The prognosis of IBC is still poor even though combination therapy with surgery, chemotherapy, and target therapy, mainly due to a lack of fully understanding of the cellular and molecular mechanisms of IBC pathogenesis and progression. In the present article, we have comprehensively reviewed the connection of the pathogenesis of IBC and inflammation, immune reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 42 publications
1
32
0
1
Order By: Relevance
“…Many studies have suggested that the activation of important inflammatory mediators such as NF-κB contributes to the aggressiveness and pathogenesis of IBC [ 19 , 20 , 21 , 22 , 23 ]. NF-κB is known to play a crucial role in tumor cell proliferation, differentiation, apoptosis, invasion, and metastasis [ 18 , 19 , 20 , 60 ]. RIPK2 is an upstream activator of NF-κB that is able to induce ubiquitination of NF-κB essential modulator.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have suggested that the activation of important inflammatory mediators such as NF-κB contributes to the aggressiveness and pathogenesis of IBC [ 19 , 20 , 21 , 22 , 23 ]. NF-κB is known to play a crucial role in tumor cell proliferation, differentiation, apoptosis, invasion, and metastasis [ 18 , 19 , 20 , 60 ]. RIPK2 is an upstream activator of NF-κB that is able to induce ubiquitination of NF-κB essential modulator.…”
Section: Discussionmentioning
confidence: 99%
“…Investigating tumor physiology through its micro-environmental biology is an attractive angle for treatment optimization. Understanding the micro-environmental imprint and its potential stereotypical response to classical anti-cancer strategies may help to define broader therapeutic combination options which could be less resistant ( 22 ) and consistent with the increasingly common paradigm of “personalizing medicine.” Indeed, some micro-environmental characteristics are rare within a subgroup of defined specific tumor patients but may be studied and better understood if present in other more frequent primary tumor subtypes. In this context, TLS have shown a common physiological pattern, which is independent from the primary tumor subtype/organs and may stimulate common strategies applicable to various cancers ( 10 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Early diagnosis and effective treatment are the hope for cancer patients. Treatments include surgery, radiation, chemotherapy, hormone therapy, immune therapy, and targeted therapy . Although these treatments are generally good, they have some side‐effect in one way or another .…”
Section: Introductionmentioning
confidence: 99%